Efficacy of a long-term pulmonary rehabilitation maintenance program for COPD patients in a real-life setting: a 5-year cohort study - Léo Blervaque; Christian Préfaut; Hélène Forthin; Francis Maffre; Marion Bourrelier; Nelly Héraud; Matthias Catteau; Pascal Pomiès; Dany Jaffuel; Nicolas Molinari; Maurice Hayot; Fares Gouzi (Respiratory Research, 2021)
Abstract Background Pulmonary rehabilitation (PR) improves exercise capacity, health-related quality of life (HRQoL) and dyspnea in chronic obstructive pulmonary disease (COPD) patients. Maintenance programs can sustain the benefits for 12 to 24 months. Yet, the long-term effects (> 12 months) of pragmatic maintenance programs in real-life settings remain unknown. This prospective cohort study assessed the yearly evolution in the outcomes [6-min walking distance (6MWD), HRQoL, dyspnea] of a supervised self-help PR maintenance program for COPD patients followed for 5 years. The aim was to assess the change in the outcomes and survival probability for 1 to 5 years after PR program discharge in COPD patients following a PR maintenance program supported by supervised self-help associations. Methods Data were prospectively collected from 144 COPD patients who followed a pragmatic multidisciplinary PR maintenance program for 1 to 5 years. They were assessed yearly for 6MWD, HRQol (VQ11) and dyspnea (MRC). The 5-year survival probability was compared to that of a control PR group without a maintenance program. A trajectory-based cluster analysis identified the determinants of long-term response. Results Maintenance program patients showed significant PR benefits at 4 years for 6MWD and VQ11 and 5 years for MRC. The 5-year survival probability was higher than for PR patients without PR maintenance. Two clusters of response to long-term PR were identified, with responders being the less severe COPD patients. Conclusions This study provides evidence of the efficacy of a pragmatic PR maintenance program in a real-life setting for more than 3 years. In contrast to short-term PR, long-term PR maintenance appeared more beneficial in less severe COPD patients.